Development of Electronic Student Worksheets Based on the Discovery Learning Model on Algebra Material - Shafwa Maitsa Adzra Tsani; Sumargiyani Sumargiyani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to assess the validity and practicality of electronic student worksheets (LKPD) based on the Discovery Learning model, using LiveWorksheets, for Algebraic Expressions in Grade VIII Junior High School students. The research follows a Research and Development (R&D) approach, employing the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SMP Muhammadiyah 6, Yogyakarta. Data were collected using expert validation instruments from subject-matter and media experts, as well as student response questionnaires. The findings reveal that the developed electronic worksheets were rated highly valid by subject matter experts (82.89%) and by media experts (94.48%). Regarding practicality, student assessments indicated 88% for small-group trials, categorized as very practical, and 79.82% for large-group trials, categorized as practical. These results indicate that the electronic worksheets are valid and practical for use in classroom instruction.